Implication of international scholars’ influence on the direction of Abdul Hadi’s political thought - Latifah Abd Majid,; Mohd Nasir Abdul Majid,; Zuliza Mohd Kusrin,; Wan Siti Norjannah W Sulong, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Influence involves a state of two-way direction or relationship between what or who is influenced and the influencer. The influencer has the capacity to cause an effect on the character, behaviour or development of someone or something. The effect or influence in this research is not limited to only the political but extends to tarbiyah, social, economic, jihad, dakwah, knowledge and thought aspects. Abdul Hadi is a recognised figure of political movement and dakwah in Malaysia and internationally. His leadership and personality in dakwah and politics is believed to have been influenced by some factors, among them, his direct and indirect interaction with international leaders and scholars. This article discusses the network and implication of the influence of international Islamic movement leaders and scholars which positively impacted Abdul Hadi’s socio-politics. This research was qualitatively designed using document analysis approach. Under protocol, in-depth and structured interview method was used and data descriptively analysed. Research findings show a positive impact by scholars and leaders of international movements on Abdul Hadi’s thought in devising and drawing up dakwah and political strategies at national and international levels.